The price is not right - Chami, Ralph; Fullenkamp, Connel; González Gómez, Andres; Hilmi, Nathalie; Magud, Nicolas E. (Frontiers in Climate, 2023)
The 2015 Paris Agreement requires all nations to combat climate change and to adapt to its effects. Countries promise to reduce their greenhouse gas (GHG) emissions through their Nationally Determined Contributions. Pledges to reduce emissions, however, have implications for economic growth. We estimate the link between economic growth and CO2 pollution levels and find that this relationship is highly nonlinear. A country's GHG emissions rise rapidly as its economic activity rises, relative to global activity, meaning that fast-growing countries contribute most heavily to current GHG emissions. Then, using real per-capita GDP as our metric, we estimate how much the carbon price should be in order to remove the economic growth benefit from excess GHG emissions. We find that the implied prices are far higher than the prices on any existing market for emissions as well as estimates of the social cost of carbon.Our findings also have important implications for the global dialogue regarding responsibility for climate mitigation as well as for the choice of policies to support mitigation efforts.